Analysis of Prolactin Gene Exon 4 Diversity in Peking, White Mojosari, and Peking White Mojosari Crossbreed - M. Indriati; C. Sumantri; T. Susanti (Faculty of Animal Science, Bogor Agricultural University, 2016)
Genetic marker linked to loci reproductive traits could be used to increase an effectiveness of improvement in animal breeding. Association between DNA polymorphism and a trait could be considered as candidate genetic marker for marker assisted selection (MAS) programs. Prolactin (PRL) is one of polypeptide hormones secreted by anterior pituitary gland in vertebrates. PRL plays an important role in onset of poultry incubation and brooding behavior. The aim of this study was to investigate the diversity of prolactin gene and to characterize the type of mutation in partial intron 3, intron 4 and exon 4 of duck prolactin gene. Blood extraction was collected from 168 ducks consisted of 19 Peking, 36 Mojosari, and 113 Peking White Mojosari (Peking Mojosari putih) ducks. Polymerase chain reaction of fragment prolactin gene exon 4 and partial intron 3 and 4 have been successfully amplified with length of base pair were 496 bp. A total of 30 µL PCR product from each sample were sequenced for forward sequence using BIOTRACE 3730 by First Base Company, Malaysia. Alignment analysis found six SNP consisted of g.3941T>G, g.3975C>A, g.4110T>C, INDEL 3724A, INDEL 34031, and INDEL 3939A. Analysis of SNP frequency result indicated mutation of INDEL 3724A, g.3941T>G, g.3975C>A, INDEL 4031A and g.4110T>A in duck sample were polymorphic and INDEL 3939A were monomorphic.